EFFECTS OF SPINACH (Amaranthus sp.) EXTRACT SUPPLEMENTATION ON MOLTING DURATION AND PHYSIOLOGICAL RESPONSES OF MUD CRABS (Scylla sp.) REARED IN CRAB APARTMENT SYSTEMS - Sutrisno, Bagas Gagat Rahina Asihing; Supriatna, Supriatna; Uzair, Hafiz Muhammad; Ismail, Azwar; Hertika, Asus Maizar Suryanto (Politeknik Kelautan dan Perikanan Jembrana, 2025)
This study investigates the effects of dietary supplementation of spinach (Amaranthus sp.) extract, rich in phytoecdysteroids, on the molting process and physiological parameters of mud crabs (Scylla sp.) cultivated in crab apartment boxes integrated with a recirculating aquaculture system. This experiment was designed using a completely randomized design (CRD) with four different doses of spinach extract as treatments (0, 300, 700, and 1000 ng g-1 of crab) and three replications. Some parameters measured were molting duration, hormone levels, including ecdysteroid and molt inhibiting hormone (MIH), reactive oxygen species (ROS), and water quality. The results showed that higher doses of spinach extract significantly shortened the molting duration (p < 0.05), with the fastest molting observed at 1000 ng g-1 (11.83 ± 1.26 days). Increased spinach extract doses also significantly affected MIH and ROS levels. Specifically, MIH levels increased from 12.05 ng mL-1 in the control to 20.88 ng mL-1 in treatment D, while ROS levels rose from 116.80 to 147.33 µmol mL-1. Overall, the administration of phytoecdysteroids from spinach presents a promising, eco-friendly approach to enhance soft-shell crab production efficiency, although careful dose optimization is necessary to balance production acceleration with animal welfare.Penelitian ini mengkaji pengaruh suplementasi pakan dengan ekstrak bayam (Amaranthus sp.) yang kaya akan fitoekdisteroid terhadap proses molting dan parameter fisiologis kepiting bakau (Scylla sp.) yang dibudidayakan dalam kotak apartemen kepiting terintegrasi dengan sistem akuakultur resirkulasi. Percobaan ini dirancang menggunakan rancangan acak lengkap (RAL) dengan empat dosis ekstrak bayam sebagai perlakuan (0, 300, 700, dan 1000 ng g⁻¹ kepiting) dan tiga ulangan. Beberapa parameter yang diukur meliputi durasi molting, kadar hormon termasuk ekdisteroid dan molt inhibiting hormone (MIH), reactive oxygen species (ROS), serta kualitas air. Hasil penelitian menunjukkan bahwa peningkatan dosis ekstrak bayam secara signifikan memperpendek durasi molting (p < 0,05), dengan waktu molting tercepat pada dosis 1,000 ng g⁻¹ (11,83 ± 1,26 hari). Peningkatan dosis ekstrak bayam juga berpengaruh nyata terhadap kadar MIH dan ROS. Secara khusus, kadar MIH meningkat dari 12,05 ng mL⁻¹ pada kontrol menjadi 20,88 ng mL⁻¹ pada perlakuan D, sedangkan kadar ROS naik dari 116,80 menjadi 147,33 µmol mL⁻¹. Secara keseluruhan, pemberian fitoekdisteroid dari bayam menunjukkan potensi sebagai pendekatan ramah lingkungan untuk meningkatkan efisiensi produksi kepiting cangkang lunak, meskipun demikian optimasi dosis tetap diperlukan agar tercapai keseimbangan antara percepatan produksi dan kesejahteraan hewan.